2012
DOI: 10.1111/j.1574-6941.2012.01311.x
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial dominance in subseafloor sediments characterized by methane hydrates

Abstract: The degradation of organic carbon in subseafloor sediments on continental margins contributes to the largest reservoir of methane on Earth. Sediments in the Andaman Sea are composed of ~ 1% marine-derived organic carbon and biogenic methane is present. Our objective was to determine microbial abundance and diversity in sediments that transition the gas hydrate occurrence zone (GHOZ) in the Andaman Sea. Microscopic cell enumeration revealed that most sediment layers harbored relatively low microbial abundance (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 60 publications
3
26
1
Order By: Relevance
“…(Blazejak and Schippers, 2010;Fry et al, 2008;Inagaki et al, 2006;Orcutt et al, 2011;Webster et al, 2004;Webster et al, 2007). JS1 often co-occurs with Chloroflexi in anoxic sediment zones (Briggs et al, 2012;Orcutt et al, 2011), which was also observed in this study. But the ecological niche for JS1-affiliated bacteria is still controversial.…”
Section: Bacterial Diversitysupporting
confidence: 73%
See 2 more Smart Citations
“…(Blazejak and Schippers, 2010;Fry et al, 2008;Inagaki et al, 2006;Orcutt et al, 2011;Webster et al, 2004;Webster et al, 2007). JS1 often co-occurs with Chloroflexi in anoxic sediment zones (Briggs et al, 2012;Orcutt et al, 2011), which was also observed in this study. But the ecological niche for JS1-affiliated bacteria is still controversial.…”
Section: Bacterial Diversitysupporting
confidence: 73%
“…The finding that organic matter influences the bacterial community structure has been observed in the Andaman Sea, the North Sea and the Arctic Mid-Ocean Ridge (Briggs et al, 2012;Jorgensen et al, 2012;Sapp et al, 2010). In this study, both TOC and TON were influencing factors for the bacterial community structure.…”
Section: Correlation Between Bacterial Community Composition and Envimentioning
confidence: 65%
See 1 more Smart Citation
“…Methane gas hydrates are widely found in continental margin sediments where methane is abundant, temperature is low, and pressure is high (Kvenvolden, 1993;Buffett, 2000;Tréhu et al, 2006). Hydrates are not uniformly distributed within sediments and their morphology depends on grain and pore size.…”
Section: Introductionmentioning
confidence: 99%
“…The limited number of microbiological studies focused on sediment of the Juan de Fuca Ridge have typically not incorporated phylogenetic marker-based surveys of community diversity such as small subunit ribosomal RNA (SSU rRNA) gene sequencing (e.g., Cragg et al, 2000;Mather and Parkes, 2000;Engelen et al, 2008); only studies focused on Cascadia margin methane hydrate-bearing sediment have incorporated such an approach (e.g., Bidle et al, 1999;Marchesi et al, 2001;Knittel et al, 2003;Inagaki et al, 2006;Nunoura et al, 2008;Briggs et al, 2012). Descriptions of the phylogenetic and metabolic composition of microbial communities from other Juan de Fuca Ridge sediment environments are important for comprehensively investigating patterns in microbial distribution and community evolution with respect to gradients in the physical and chemical properties of the system.…”
Section: Introductionmentioning
confidence: 99%